Intelligent Nanomaterials for Solar Energy Harvesting: From Polar Bear Hairs to Unsmooth Nanofiber Fabrication - Wang, Qingli; He, Ji-Huan; Liu, Zhi (Frontiers in Bioengineering and Biotechnology, 2022)
Polar bears can live in an extremely cold environment due to their hairs which possess some remarkable properties. The hollow structure of the hair enables the bear to absorb energy from water, and the white and transparent hairs possess amazing optical properties. However, the surface morphology function of bear hairs has been little-studied. Herein, we demonstrate that the micro-structured scales distributed periodically along the hair can absorb maximal radiative flux from the Sun. This polar bear hair effect has the ability for the hair surface not to reflect radiation with a wavelength of about 500 nm. Mimicking the polar bears’ solar performance in the fabrication of nanofibers will certainly stimulate intelligent nanomaterials for efficient solar energy absorption. Therefore, a new technology is discussed in this work for the fabrication of periodic unsmooth nanofibers toward solar energy harvesting.